Impact of brand positioning on customer loyalty: A systematic review - Wilmer Alberto Pachau Torres; Luis Miguel Romero Echevarria; Fernando Emilio Escudero Vilchez; Silvia Liliana Salazar Llerena; Clefort Bachan Alcantara Cuadrado; Wilfredo Pablo Quiroz Cristóbal; Pedro Antonio Arevalo Martinez (International Journal of Medical Toxicology and Legal Medicine, 2024)
The purpose of this study was to generate theoretical knowledge that would contribute to a deeper understanding of the impact of brand positioning on customer loyalty. This analysis reviewed the literature using the PRISMA methodology, opting for a qualitative approach methodology, framed in the basic type. Applying the keywords, 82 publications were found in ScienceDirect, EBSCOhost and Web of Science, in which 21 relevant articles were analyzed for evaluation. The findings show that a clear and consistent brand positioning strengthens customer loyalty by building trust and encouraging repurchase. The review shows that consistent brand positioning strengthens customer loyalty by building trust. In addition, technology and global strategies are crucial to maintain brand relevance.